The Role of Fintech Lending in Expanding Sharia Financial Inclusion and Human Development in Indonesia - Hakim, Lukman; Prawwatya, Nurrahma; Huda, Choirul; Fadila, Dimas Fajar Safa; Rizaldi, Muhammad (Share: Jurnal Ekonomi dan Keuangan Islam, 2024)
This study investigates the impact of fintech peer-to-peer (P2P) lending on community well-being in Indonesia by analyzing its role in promoting Sharia financial inclusion. Using a quantitative approach, the research analyzes secondary data from 33 provinces in Indonesia spanning 2021-2022. The study employs panel data regression to assess the effects of fintech P2P lending borrower accounts and Gross Regional Domestic Product (GRDP) on Sharia financial inclusion. Additionally, Pearson's correlation analysis examines the relationship between Sharia financial inclusion and the Human Development Index (HDI). The findings reveal that both the number of borrower accounts and GRDP positively and significantly influence Sharia financial inclusion. Furthermore, the study demonstrates a positive correlation between Sharia financial inclusion and HDI. These results suggest that fintech P2P lending in Indonesia, by directing funds towards productive businesses, contributes to the improvement of community well-being through enhanced Sharia financial inclusion.========================================================================================================ABSTRAK – Peran Fintech Lending dalam Memperluas Inklusi Keuangan Syariah dan Pembangunan Manusia di Indonesia. Penelitian ini mengkaji pengaruh fintech peer-to-peer (P2P lending) terhadap kesejahteraan masyarakat di Indonesia dengan menganalisis perannya dalam mendorong inklusi keuangan syariah. Menggunakan pendekatan kuantitatif, penelitian ini menganalisis data sekunder dari 33 provinsi di Indonesia selama periode 2021-2022. Penelitian ini menggunakan regresi data panel untuk menilai pengaruh jumlah akun peminjam fintech P2P lending dan Produk Domestik Regional Bruto (PDRB) terhadap inklusi keuangan syariah. Selain itu, analisis korelasi Pearson digunakan untuk menguji hubungan antara inklusi keuangan syariah dan Indeks Pembangunan Manusia (IPM). Hasil penelitian menunjukkan bahwa jumlah akun peminjam dan PDRB berpengaruh positif dan signifikan terhadap inklusi keuangan syariah. Lebih lanjut, penelitian ini menunjukkan korelasi positif antara inklusi keuangan syariah dan IPM. Temuan ini menunjukkan bahwa fintech P2P lending di Indonesia, dengan menyalurkan dana ke bisnis produktif, berkontribusi pada peningkatan kesejahteraan masyarakat melalui peningkatan inklusi keuangan syariah.